EATING DISORDERS IN CHILDREN AND ADOLESCENTS WITH TYPE 1 DIABETES: A LITERATURE REVIEW - Kamila Mozga; Olga Synowiecka; Igor Rydzyk; Anna Szuciak; Julia Szewczyk; Anna Marek; Wiktor Milewczyk; Ewelina Wieczorek; Michał Świta; Konrad Talarek; Mateusz Jasiński; Michał Szalach (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Diabetes affects over 422 million people worldwide, with Type 1 Diabetes (T1D) increasing by 3–4% annually, particularly in children. Effective T1D management requires lifelong insulin therapy, which is psychologically demanding and may contribute to Disordered Eating Behaviors (DEB). Such behaviors heighten the risk of developing diabetes-specific eating disorders. Materials and Methods: A systematic literature search of PubMed (2020–2024) identified case-controlled studies examining the occurrence (n=5) or risk (n=4) of eating disorders (EDs) among children and adolescents with T1D. Results: Across 3025 T1D patients, 861 (28.5%) were diagnosed with EDs. Females were more frequently affected (496; 57.6%) than males (331; 38.4%). Risk-focused studies involving 612 patients found 199 at risk of developing EDs, with a similar predominance among females (63; 31.7%) compared to males (62; 31.2%). Conclusions: This review underscores the high prevalence and risk of EDs in children and adolescents with T1D, with females disproportionately affected. These disorders are strongly associated with anxiety, depression, insulin omission, and restrictive eating, contributing to poor glycemic control. Vigilant monitoring, particularly through HbA1c measurement, is essential. Early recognition of symptoms and the integration of comprehensive psychological support into diabetes care are crucial for prevention and management. Strategies such as establishing structured routines, encouraging physical activity, and promoting stress management may mitigate the risk of ED. Addressing these challenges is imperative for optimizing both metabolic and psychological outcomes in young patients with T1D.